Association between selected trace elements and body mass index and waist circumference: A cross sectional study. Issue 2 (March 2019) - Zohal, Mahnaz; Jam-Ashkezari, Saeedeh; Namiranian, Nasim; Moosavi, Amin; Ghadiri-Anari, Akram
Abstract: Background: The prevalence of obesity has increased worldwide. Abnormal plasma level of some trace elements may be associated with obesity. The present study was designed to compare the plasma level of zinc, phosphate, calcium and magnesium with the degree of body mass index and waist circumference. Material and methods: In this cross sectional study 149 persons (20–60 years old) from March 2014 till April 2017 were included. Definition of central obesity was waist circumference (WC)≥ 102 cm and ≥88 cm in men and women, respectively. Also BMI categorized to: normal weight: 18.50–24.99, overweight: 25.00–29.99 and obese: ≥30 kg/m2 respectively. Mg, Ca, P and Zinc in plasma was checked after12 h fasting in each persons. Comparison between the level of Mg, P, Ca and Zinc by three categories of BMI or waist circumference performed. The data were analyzed by independent T-test and one-way ANOVA. Scheffe method was used to determine post-hoc pair-wise comparisons. The relationship between BMI and concentration of elements was detected by linear correlation and Cubic model. A p ≤ 0.05 were considered statistically significant. Statistical analyses were executed by SPSS version 20. Results: In this study, 32.2% male and remainder female, mean age of 42.26 ± 13.03 were participated. 40.9% were normal and 59.1% obese base on waist circumference. Also 24.8% normal, 44.3% overweight and remainder was obese according to BMI. Obese subjects base on waist circumference had significantly lower serum Zinc(pvalue:0.002), Ca (pvalue:0.0001)and Mg(pvalue:0.042) concentration. Whereas, P concentration was significantly higher in obese cases in comparison with normal subjects(pvalue:0.012). Also normal cases had significantly higher serum Zinc (pvalue: 0.0001), Ca (pvalue:0.0001), and Mg(pvalue:0.006) concentration compared to overweight and obese subjects according to BMI categorizes. Conclusion: Inverse correlation present between plasma zinc, calcium and magnesium level and BMI and waist circumference, but positive correlation seen between P level and waist circumference. Further studies are needed to evaluate the effect of dietary or supplemental interventions on obesity and central obesity.